Research based undergraduate science teaching - Sunal, Dennis W.; Sunal, Cynthia Szymanski; Wright, Emmett L.; Mason, Cheryl L.; Zollman, Dean (Research in science education., 2014)
Research in Science Education (RISE) Volume 6, Research Based Undergraduate Science Teaching examines research, theory, and practice concerning issues of teaching science with undergraduates. This RISE volume addresses higher education faculty and all who teach entry level science. The focus is on helping undergraduates develop a basic science literacy leading to scientific expertise. RISE Volume 6 focuses on research-based reforms leading to best practices in teaching undergraduates in science and engineering.The goal of this volume is to provide a research foundation for the professional development of faculty teaching undergraduate science. Such science instruction should have short- and longterm impacts on student outcomes. The goal was carried out through a series of events over several years. The website at http://nseus.org documents materials from these events. The international call for manuscripts for this volume requested the inclusion of major priorities and critical research areas, methodological concerns, and results of implementation of faculty professional development programs and reform in teaching in undergraduate science classrooms.In developing research manuscripts to be reviewed for RISE, Volume 6, researchers were asked to consider the status and effectiveness of current and experimental practices for reforming undergraduate science courses involving all undergraduates, including groups of students who are not always well represented in STEM education. To influence practice, it is important to understand how researchbased practice is made and how it is implemented. The volume should be considered as a first step in thinking through what reform in undergraduate science teaching might look like and how we help faculty to implement such reform.